2023
DOI: 10.1007/s40272-023-00558-x
|View full text |Cite
|
Sign up to set email alerts
|

What Role for Long-Acting Injectable Antipsychotics in Managing Schizophrenia Spectrum Disorders in Children and Adolescents? A Systematic Review

Abstract: Background Long-acting injectable antipsychotics (LAIAs) are an efficacious and well-tolerated treatment in adults with schizophrenia spectrum disorders (SSD). However, there is less evidence for their use in children and adolescents. Objectives The aim of this systematic review was to summarize findings regarding the effectiveness and side effects of LAIA in children and adolescents with SSD. Methods Four databases (Web of Science, PubMed, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 80 publications
0
7
0
4
Order By: Relevance
“…Only when the data was pooled for the entire 12 months of follow-up was there a significant difference with fewer readmissions in the LAIA group when compared with the oral comparator group. 6 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only when the data was pooled for the entire 12 months of follow-up was there a significant difference with fewer readmissions in the LAIA group when compared with the oral comparator group. 6 …”
Section: Discussionmentioning
confidence: 99%
“… 2 When comparing schizophrenia spectrum disorders (SSD) in pediatric and adult patients, pediatric patients are reported to have worse outcomes linked to severe cognitive deficits, social impairment, relapses, and hospitalizations. 6 Whereas limited studies conclude that there may be improved clinical outcomes and adherence with using LAIAs when compared with oral counterparts, the lack of data supporting LAIA use in this population may lead to lower use of these formulations. 1 A meta-analysis of studies involving pediatric patients with SSD found clinical improvement of patients using LAIA formulations in up to 12 months of follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations